ابن رزيق وإنتاجه الفكري. - الهاشمي, سعيد محمد (المجلة العربية للعلوم الإنسانية, 2000)
يهدف هذا البحث إلى التعريف بالمؤرخ الأديب العماني حميد بن محمد بن رزيق بن سعيد بن غسان النخلي، والمعروف بابن رزيق، والمشهور عند الكتاب الأجانب بسليل ابن رزيق ، فيعالج هذا البحث حياة هذا المؤرخ والأديب، وعلاقته مع حكام آل بوسعيد في عمان؛ وذلك من خلال إلقاء الضوء على التراث الأدبي الذي خلفه في شتى الفنون الأدبية التاريخية، والتي بلغت مؤلفاته فيه سبعة عشر مؤلفا؛ نصفها في التاريخ، ومعظمها الآن مبعثرة في مكتبات العالم . اشترك ابن رزيق في حروب السيد سعيد بن سلطان، وتقلد بعض المناصب الإدارية في مدينة مسقط، كما أنه كان صديقاً حميماً للسيد سالم بن سلطان، ثم لأبنائه حمد ومحمد من بعد وفاته. أما مؤلفات ابن رزيق فقسمت إلى ثلاثة أقسام: المقامات والشعر والتاريخ. لم يطبع من هذه المؤلفات سوى ثلاثة كتب: الفتح المبين، والشعاع الشائع، وديوانه سلك الفريد. واختيرت بعض قصائده فطبعت تحت عنوان: ديوان ابن رزيق . والكتابان المشهوران لابن رزيق على الإطلاق هما: الصحيفة العدنانية، والصحيفة القحطانية، ويعدان من الكتب المهمة في التاريخ العماني، والكتاب الأخير تبلغ عدد صفحاته 957 صفحة، وما زالت مخطوطة في جامعة أكسفورد. وقد توقف ابن رزيق عن الكتابة بعد تصنيف كتابه بدر التمام، وذلك عندما بلغ من العمر نحو السبعين سنة.

Oman's relations with Bahrain and Kuwait (1744 - 1804) - Hashimy, Sa'id b. Muhammad (Journal of the Gulf and Arabian Peninsula Studies, 2000)
يهدف هذا البحث إلى إبراز نوع العلاقة بين عمان وبين البحرين والكويت خلال النصف الثاني من القرن الثامن عشر للميلاد .حيث كانت البحرين تابعة لعمان لمدة تزيد عن عشرين عاما اعتبارا من 1717، ولكن نتيجة للمشاكل التي اجتاحت عمان في مرحلة انهيار دولة اليعاربة ، وطموحات نادر شاه في الخليج ال أدت إلى خضوع البحرين للفرس . وكان على رأس السلطة في عمان في النصف الثاني من القرن 18م الإمام أحمد بن سعيد البوسعيدي الذي تم تنصيبه بعد انهيار دولة اليعاربة سنة 1749م . حكم أحمد بن سعيد عمان لمدة 34 سنة ، وشهدت فترة حكمه أحداث مهمة من استقرار آل صباح في الكويت وآل خليفة في الزبارة ثم انتقلوا إلى البحرين بعد فتحها عام 1783م . كما عاصر شموخ دولة كريم خان في إيران وتطلعه نحو البصرة ومحاصرتها أكثر من سنتين بين عامي 1775و1776م ، ودور أحمد بن سعيد في مساعـدة أهل البصرة في فك الحصار . واتصفت العلاقة بين الإمام أحمد والعتوب بأنها علاقة ودية وحميدة . وبعد وفاة الإمام أحمد بن سعيد عام 1783م ، اجتاحت عمان موجة من الاضطراب السياسي بين أبناء الإمام أحمد ، وتمخض عن ذلك تسوية بين الاخوة الثلاثة ، وآل أمر عمان إلى سلطان بن أحمد الذي رضى بمسقط عاصمة له . وبدأ نشاطه في ضم مجموعة من جزر الخليج وقاد طموحه نحو الاستيلاء على البحرين وتهديد الكويت ، لكن حاميته التي وطنها عام 1800م في البحرين لم تجد أرض صلبة بل ثار عليه آل خليفة ، بمساندة السعوديين .
Keywords: Politique étrangère -- Oman; Relations -- Oman -- Bahrein; Relations -- Oman -- Koweit; Vie politique -- Oman

Indo - Arabian maritime contacts during the bronze age : scientific study of pottery from Ras al-junayz : Oman - Vishwash, Gogte D. (أدوماتو, 2000)
Keywords: Archéologie -- Oman

Je suis appelé à Zanzibar - Remillieux, Daniel (Rimbaud vivant, 2000)
Keywords: Récits de voyage -- Zanzibar

Narrative representations of revolutionary Zanzibar - Myers, Garth Andrew (Journal of Historical Geography, 2000)
Increasingly, geographers use literature and popular culture to interpret the ways in which historical events are represented and remembered. One goal of this usage of literature is the expansion of the prevailing scholarly imagination beyond western scripts to appreciate the nuances of interpretation which accompany any major world event. Here, I develop a cultural materialist study of narratives of Zanzibar's 1964 Revolution with a focus on accounts originating in Tanzania. These representations of history are assessed as dominant, residual, emergent and excluded accounts in a contest for cultural hegemony, emphasizing themes of place description and racial identity. Storytelling about Zanzibar's revolution evidences the layers of meaning in representations of history and highlights the shifting power dynamics and historical geography of cultural narratives. Such a multi-layered analysis is necessary because the revolution narrative is not an idle memory or an uncontested tale. It is at the core of many Zanzibaris» political identity. Zanzibar represents a microcosm of many of the world's most pressing social and geopolitical concerns, providing a valuable lesson in the intricacies of imagined communities and the imagined histories which accompany them.
Keywords: Vie politique -- Zanzibar -- 1963-1964

موقف بريطانيا من ثورة الإمامة في عمان 1913م - الحسيني, فاضل محمد (الوثيقة, 2000)
Keywords: Vie politique -- Oman -- 1913-1932

العلاقات الثقافية بين عمان و بلاد المغرب من الفتح الإسلامي حتى القرن الثامن الهجري - بوتشيش, إبراهيم القادري (المجلة العربية للعلوم الإنسانية, 2000)

المنشآت الدينية بمدينة سدراته (ورقلة) ‏ ملاحظات أولية حول المسجد الجامع - حملاوي, علي (بحوث, 2000)
إذا كان البحث هو طلب الحقيقة العلمية وتقصيها وإذاعتها في الأوساط العلمية فلا بد لهذا البحث من منهج وطريقة يسير عليها ليصل إلى الحقيقة في موضوع من الموضوعات الأدبية أو القضايا المتعلقة بها. وكان هذا المقال أحد أهم الملاحظات حول احد المنشآت الدينية في مدينة سدراتة، وهي لا تعدو أن تكون محاولة لإطلاع ذوي الاختصاص عما تحتفظ به المدينة من كنوز ونحن على يقين بأن ما ستسفر عنه نتائج ‏الحفريات اللاحقة ستزيدنا اطلاعا ومعرفة حول هذا المعلم..

The Architecture of Bilad Manh in Central Oman - Bandyopadhyay, Soumyen (Archéologie Islamique, 2000)
Keywords: Archéologie -- Oman

قائمة المستظهرين لكتاب الله 1420-1421هـ\1999-2000م (الحياة, 2000)
Keywords: Coran -- apprentissage

من حصاد المطابع (الحياة, 2000)

الثابت والمتغيّر في قانون الأسرة - أبو بكر, صالح بن عبد الله (الحياة, 2000)

الإفتتاحية - الحسني, محمد الهادي (الحياة, 2000)

الشيخ علي يحي معمر وفكره العقدي - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2000)
Keywords: Muʿammar, Ali Yahya (19XX-1984)

حول رحلتي الشيخ أبي إسحاق زنجبار - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2000)
Keywords: Récits de voyage -- Zanzibar

أبو إسحاق إبراهيم أطفيس - الفاسي, علال (الحياة, 2000)
Keywords: Biographies -- Mzab -- 20e siècle

البعد الواقعي في التفسير الشفاهي: تفسير الشيخ بيوض نموذجا - الوزناجي, نادية (الحياة, 2000)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

مرويات الإمام جابربن زيد في الكتب التسعة( جرد و تحليل) - بابا عمي, محمد بن موسى (الحياة, 2000)

الفكر السياسي عند الرسميّين - بحاز, إبراهيم بن بكير (الحياة, 2000)

من أجل إستراتيجية وطنيّة لحماية المخطوط - بوتردين, يحيى بن صالح (الحياة, 2000)
Keywords: Manuscrits -- Conservation; Manuscrits -- Mzab

ملاحظات حول كتابة السيرة النبوية - بوحجام, محمد بن قاسم ناصر (الحياة, 2000)

أين عقلك؟ بحث في موقع العقل - حريزي, موسى بن إبراهيم (الحياة, 2000)

القاعدة التجارية بين الشريعة والقانون - حمدي, محمد بن صالح (الحياة, 2000)

قوّة الذاتية في أدب زكي مبارك - حواش, مصطفى بن بكير (الحياة, 2000)

في رحاب السنّة - شريفي, سعيد بن بالحاج (الحياة, 2000)

رسالة إلى الشهيد الدكتور عمرو النامي - فخار, حمو بن عمر (الحياة, 2000)

حول كتاب "الإمامة عند الإباضية" للشهيد بكير وعلي - قسوم, عبد الرزاق (الحياة, 2000)
Keywords: Recension

رسالة حامل القرآن - وينتن, مصطفى بن الناصر (الحياة, 2000)

الرسائل الجامعية (الحياة, 2000)

قائمة المستظهرين لكتاب الله العزيز (الحياة, 2000)
Keywords: Coran -- apprentissage

رسالة الأحياء - أوبكة, أحمد بن عمر (الحياة, 2000)

وقفة تعريفية للإباضية في دولة تنزانيا وجزيرة زنجبار - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2000)

القرآن والعصر - بابا عمي, محمد بن موسى (الحياة, 2000)

مدخل إلى الإنفراج من خلال سير سدراتة ووارجلان - بابا عمي, محمد بن موسى (الحياة, 2000)

محطوط العدد :كتاب المعلقات في حكايات أهل الدعوة - بابزير, سليمان بن إبراهيم (الحياة, 2000)
Keywords: Bin Ya'lâ, mosquée (Erriadh, Djerba); Monuments -- Djerba

يا صفوة الرحمان - باجو, صالح بن إبراهيم (الحياة, 2000)
Keywords: Poésie -- Mzab

المنهج التربوي في القرآن الكريم - باجو, مصطفى بن صالح (الحياة, 2000)

إشكالية السر والعلن في الدعوة المحمدية - بحاز, إبراهيم بن بكير (الحياة, 2000)

التواصل الثقافي بين عمان والجزائر - بوحجام, محمد بن قاسم ناصر (الحياة, 2000)
Keywords: Relations -- Oman -- Mzab

حياة مع القرآن - حدبون, صالح بن أحمد (الحياة, 2000)

من تراثنا الحضاري: الأوقاف الخيريّة لمسجد القرارة - حمدي, محمد بن صالح (الحياة, 2000)
Keywords: Waqf (fondations) -- Mzab

المنهج التربوي في القرآن الكريم - فخار, حمو بن عمر (الحياة, 2000)

مناقب القائد المربّي : الشيخ إبراهيم بيّوض - فخار, حمو بن عمر (الحياة, 2000)

الهبة والعدالة بين الأولاد - كروم, أحمد بن حمو (الحياة, 2000)

الإفتتاحية: من بذور الحياة إلى شجرتها الوارفة - كعباش, محمد سعيد (الحياة, 2000)

البعد التربوي والإجتماعي في فكر الشيخ بيوض - مختار, محي الدين (الحياة, 2000)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

القرآن والطفل - ناصر, محمد صالح (الحياة, 2000)

Review of Zanzibar: A Plan for the Historic Stone Town; Doors of Zanzibar - Frankl, P.J.L. (British Journal of Middle Eastern Studies, 2000)
Keywords: Recension

Oman Under Qaboos: From Coup to Constitution, 1970-1996; Calvin Allen, Jr.; W. Lynn Rigsbee II - Farah, Caesar E. (Digest of Middle East Studies, 2000)
Keywords: Recension

Review of Changing Rural Systems in Oman. The Khabura Project - Pater, Ben de (GeoJournal, 2000)
Keywords: Recension

A Survey between Quriyat and Sur in the Sultanate of Oman (1997) - Ibrahim, Moawiyah; ElMahi, Ali Tigani (Proceedings of the Seminar for Arabian Studies, 2000)
The survey was carried out in advance of plans to replace the present track by a paved road, and was designed both to discover new sites and relocate those already known, and to draw up a programme for the study of the archaeology of the area and for the restoration and protection of its sites. The balance between natural and cultural heritage, one the one hand, and economic development on the other, is always critical. During the course of the survey sites of many different types and dates, from prehistoric shell middens to medieval mosques, were visited and assessed. Several sites have been noted as of special interest or in particular danger, and recommendations for further work are presented.
Keywords: Archéologie -- Oman

الحملات الفارسية على عمان و سقوط حكم اليعاربة 1149 - 1162هـ / 1737 - 1749م - السديس, عبدالرحمن بن علي بن عبدالله (مجلة جامعة الإمام محمد بن سعود الإسلامية, 2000)
Keywords: Relations -- Oman -- Iran

Ninth-Century Muslim Anarchists - Crone, Patricia (Past & Present, 2000)
Keywords: Najdiyya

The Serpent in the traditional culture of - Vitaly Naumkin.pdf - Naumkin, Vitaly; Porkhomovsky, Victor (Proceedings of the Seminar for Arabian Studies, 2000)
Keywords: Zanzibar

Genetic structure of north-west Africa revealed by STR analysis - Bosch, Elena; Calafell, Francesc; Pérez-Lezaun, Anna; Clarimón, Jordi; Comas, David; Mateu, Eva; Martínez-Arias, Rosa; Morera, Bernal; Brakez, Zahra; Akhayat, Omar; Sefiani, Abdelaziz; Hariti, Ghania; et al. (European Journal of Human Genetics, 2000)
Keywords: Génétique -- Afrique du Nord

Aufbau eines Planungsinformationssystems für das Vallée M’zab = Elaboration d‘un système d‘information pour la planification urbaine de la Vallée M’zab - Benyoucef, Brahim; Benouar, Mohamed; Honermann, Helmut (Trialog, 2000)
Keywords: Urbanisme -- Mzab

جمعية التراث بالقرارة ومشروعها الطموح لحماية المخطوطات في منطقة وادي ميزاب - عوفي, عبد الكريم (آفاق الثقافة والتراث, 2000)
Keywords: Manuscrits -- Conservation; Manuscrits -- Mzab

New Prehistoric sites along the Omani coast from Ra’s al-Hadd to Ra’s al-Jins - Usai, Donatella (Arabian Archaeology and Epigraphy, 2000)
Keywords: Archéologie -- Oman

La Russia e la guerra di Libia, 26 agosto - 5 novembre 1911 - Onelli, F. (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 2000)

Teşkilat-ı Mahsusa Kuzey Afrika’da (1914-1918) - Pehlivanlı, Hamit (Atatürk Araştırma Merkezi Dergisi, 2000)

Saiyid Sa’id bin Sultan Al Bu Sa’id of Oman (1791-1856) and his relationships with Europe - Nicolini, Beatrice (ARAM Periodical, 2000)
A study of Sayyid Saʿīd’s relations with Great Britain and France, within the framework of the rivalry between these two countries in the Indian Ocean, and Sayyid Saʿīd’s policy towards the British demand for abolition of the slave trade.
Keywords: Zanzibar

Qirā’a ūlà li-Maqāmāt al-Barwānī - Bū ʿAlī, Asya bint Nāṣir al- (نزوى: مجلة فصلية ثقافية, 2000)

Min Farā’id al-Turāth al-ʿUmānī: al-Amālī al-ʿUmāniyya - Banʿalī, Būʿallām Būzayyān (نزوى: مجلة فصلية ثقافية, 2000)

Muḥāwala li-Kitābat Sīrat al-Shaykh al-Sālimī al-Dhātiyya (al-ūlà) ʿabra Tasā’ulāt Manhajiyya fī ‘l-Mīrāth al-ʿUmānī - Azri, Khalid al- (نزوى: مجلة فصلية ثقافية, 2000)
Keywords: Biographies -- Oman

Taʿaddudiyyat al-ʿAwtabī wa-Tarjamatuhu aw Ishkāliyyāt Shakhṣiyyat al-ʿAwtabī al-Ṣuḥārī - Salimi, Abdulrahman al- (نزوى: مجلة فصلية ثقافية, 2000)
A discussion on al-ʿAwtabī’s name and genealogy. Sālimī reaches the conclusion that there were two persons with the name Salma b. Muslim al-ʿAwtabī, one with the Kunya Abū ‘l-Mundhir and the other with the Kunya Abū Ibrāhīm. See Mashriq, Ṣuḥārī, Abū ‘l-Mundhir Salāma (Salma) b. Muslim: K. Ansāb al-ʿArab.

Iḍā’āt min al-Shiʿr al-ʿUmānī: al-Mawḍūʿāt al-Taqlīdiyya qabla ‘l-Nahḍa - Mūsawī, Shabr b. Sharaf al- (نزوى: مجلة فصلية ثقافية, 2000)
Short examples of poetry from the following poets: Khālid b. Hilāl [b. Sālim b. Māniʿ] al-Raḥabī [al-Sarūrī] (1908-1953); Aḥm. b. Ḥamdūn [b. Ḥumayyid b. ʿAbdl.] al-Ḥārithī (1906-1966); Hilāl b. Badr [b. Sayf] al-Būsaʿīdī (1903-1966); [Abū Hilāl] Sālim b. Ḥamūd al-Siyābī [al-Samā’ilī] (d. 1994); Abū ‘l-Ṣūfī Saʿīd b. Musallim al-Majīzī [al-Samā’ilī] (1864-1953); Ṣāliḥ b. ʿĪsà al-Ḥārithī (d. 1987); ʿAbdl. b. Muḥ. al-Ṭā’ī (1927-1973).
Keywords: Poésie -- Oman

li’l-Shaykh Saʿīd b. Khalfān al-Khalīlī al-mutawaffà 1287 li’l-Hijra, Naṣṣ fī ‘l-Sulūk al-ʿUmānī - Khāliṣ, Walīd Maḥmūd (نزوى: مجلة فصلية ثقافية, 2000)
An introduction on Omani Sulūk works, a few words on al-Khalīlī’s life and works, followed by the text of: Sharḥ al-Muḥaqqiq al-Khalīlī li-baʿḍ Abyāt Mīmiyyat b. al-Fāriḍ (see Mashriq, Kharūṣī, Abū Muḥ. Saʿīd b. Khalfān b. Aḥm. b. Ṣāliḥ al-Khalīlī).

Muḥāwala li-Kitābat Sīrat al-Shaykh Nūr al-Dīn al-Sālimī al-Dhātiyya. Īḍāḥāt ʿalà Aḥdāth al-Ḥawqayn - Khaḍūrī, Shaykhān b. Muḥammad al- (نزوى: مجلة فصلية ثقافية, 2000)

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Ibrahim (International Journal of Middle East Studies, 2000)
Keywords: Recension

Synthèse historique: la presse arabe de Tunisie (fin du XIXe debut du XXe s.). Une litérature de combat pour l’émancipation du peuple et la libération du pays. - Dabbab, Mohamed (Revue d'Histoire Maghrébine, 2000)
Keywords: Journalisme -- Djerba

Harmuz and the ʿUmānī and Arabian world (fifteenth century) - Piacentini Fiorani, Valeria (Proceedings of the Seminar for Arabian Studies, 2000)

Sorting out the Tribes: The Creation of Racial Identities in Colonial Zanzibar's Newspaper Wars - Glassman, Jonathon (The Journal of African History, 2000)
on the debates and discussions by which Zanzibari intellectuals crafted locally compelling concepts of racial nationalism. These debates occurred in two phases. The first involved promotion of the idea of exlusionary ethnic nationalism. This was accomplished largely by the elite literati, affiliated with the Arab Association and Zanzibar National Party, who immagined a national community defined by class-bound criteria of arabocentric “civilization”. In the second phase, poorly educated propagandists affiliated with the African Association countered with their own vision of exclusionary ethnic nationalism, one that immagined the nation in explicitly racial terms. Most of the article phocuses on the second of these phases, examining debates from the popular newspapers of the 1950s, [especially the racial nationalists of Afrika Kwetu and the elite nationalists of Mwongozi. The latter was edited by Ali Muhsin al-Barwani].
Keywords: Zanzibar

A tale of three shambas. Part II. - Bang, Anne K.; Vikør, Knut S. (Sudanic Africa, 2000)
In this article three cases before the Sultan’s Court for Zanzibar and Pemba are presented over inheritance involving the possession of shambas, farms and farmhouses in the agricultural areas (from the Zanzibar National Archive, files HC8/1-140). For the Ibāḍiyya, the main legal text was K. al-Nīl wa-Shifā’ al-ʿAlīl of ʿAbd al-ʿAzīz b. Ibr. al-Muṣʿabī al-Thamīnī (1130-1223/1718-1808). To this, the most frequently used commentary was Sharḥ al-Nīl by Muḥ. b. Yūsuf Iṭfayyish (1260-1332/1820-1914). Another much used work on Ibāḍī inheritance law was the Mukhtaṣar by the Omani author Abū ‘l-Ḥasan ʿAlī b. Muḥ. al-Bisyawī. Pp. 8-9: information on the Ibāḍī Qāḍī ʿAlī b. Muḥ. al-Mundhirī (1866-1925).
Keywords: Zanzibar

min Maṣādir al-Tārīkh wa’l-Thaqāfa, al-Siyar al-ʿUmāniyya - Salimi, Abdulrahman al- (نزوى: مجلة فصلية ثقافية, 2000)

Redrawing the Boundary between India and Britain: The Succession Crisis at Zanzibar, 1870–1873 - Blyth, Robert J. (The International History Review, 2000)
The succession crisis in Zanzibar, which eventually brought Barghash b. Saʿīd to the throne, and its broader significance, being the disputes over foreign policy between the government of India and the government of Bombay, and the rivalries between both of them and the foreign office and the colonial office.
Keywords: Vie politique -- Zanzibar

Formation and transformation processes of oasis settlements in the Sultanate of Oman: preliminary report on a new field project - Häser, Jutta (Proceedings of the Seminar for Arabian Studies, 2000)
Keywords: Archéologie -- Oman

Géostratégie : Oman : cap sur l'Océan Indien - Sobh, Samir (Arabies, 2000)

The re-naming of Oman’s highest mountain - Insall, David (Journal of Oman Studies, 2000)

The small long-handled axes of Oman - Insall, David (New Arabian Studies, 2000)
Keywords: Archéologie -- Oman

From the twilight of cultural memory: the būmah in the mosques of central Oman - Bandyopadhyay, Soumyen (Proceedings of the Seminar for Arabian Studies, 2000)
Keywords: Architecture -- Oman

الأقليّة اليهودية بجزيرة جربة بين الخرافات والواقع التاريخي - بن ساسي, يوسف (المجلة التاريخية المغربية, 2000)
Keywords: Judaïsme -- Djerba

قراءة منهجية في أحاديث الخوارج - الهلالي, ابي اسامة سليم بن عيد (الأصالة, 2000)
Keywords: Kharijisme

نشاط الخوارج السياسي في العصر الاموي - الندوي, محمد مظهر عالم (الداعي, 2000)
Keywords: Kharijisme

احسان عباس وتحقيق الشعر - بكار, يوسف حسين (جذور, 2000)
Keywords: poésie kharijite

الخطاب التربوي عند الإباضية دراسة تحليلية - رمضان, صلاح السيد (مجلة كلية التربية, 2000)
Keywords: Enseignement -- Ibadisme

Document relatif à la minorité noire à Djerba au milieu du XIXe siècle - Ben Tahar, Jamel (Revue d'histoire Maghrébine, 2000)
Keywords: Taxes -- Djerba

Le Gargoulettes (orci perforati) per la pesca del polpo a Gerba (Tunisia) Iniziando una missione etnoarcheologica - Lugli, Francesca; Vidale, Massimo (Archeologia Postmedievale, 2000)
Keywords: Archéologie -- Djerba

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Bonner, Michael (Journal of the American Oriental Society, 2000)
Keywords: Recension

Legislation and legitimation in Oman: the Basic Law - Siegfried, Nikolaus (Islamic Law and Society, 2000)
When Sultan Qabus issued Decree 101 on November 6, 1996, Oman was the last Arab country to implement a constitutional document. However, the political impact of this document is controversial: Whereas some consider the Basic Law a step towards democratization, others see merely a continuation of traditional policies. In this article I investigate the innovative potential of the Basic Law. Against the background of Omani and regional history and European and Islamic constitutional thought, I review the Decree with regard to authority and legitimation. I suggest that the law is mainly symbolic in character. It exploits tribal and Islamic concepts to create a historically unfounded notion of a homogeneous state. The civil liberties it grants do not extend to the public sphere. I conclude that Oman's Basic Law does nothing more than to freeze the status quo, according to which the Sultan remains the only recognized authority in the state.
Keywords: Vie politique -- Oman -- 1970-2020

Nazionalismo e collaborazionismo in Libia: i colloqui di Tripoli (novembre 1912) - Bernini, Simone (Journal of Libyan Studies, 2000)
Keywords: Invasion italienne -- Libye

The mudsnail genus Hydrobia s.s. in the northern Atlantic and western Mediterranean: a phylogenetic hypothesis - Wilke, T.; Rolán, E.; Davis, G. M. (Marine Biology, 2000)
The mudsnail taxon Hydrobia s.l. plays a major role in numerous ecological and parasitological studies. Yet, its taxonomy is confusing and its biogeography is poorly understood. A principal problem is that taxa of Hydrobia s.l. belong to morphostatic radiations – widely allopatric species radiations with little or no habitat diversification and a low level of anatomical change. So far, three morphostatic radiations can be identified within Hydrobia s.l.: Hydrobia s.s., Peringia, and Ventrosia. These radiations are identical with the putative genera of Hydrobia s.l. The purpose of the paper is to infer phylogenetic relationships within one of these radiations, Hydrobia s.s. in the northern Atlantic and western Mediterranean. A total of 22 populations, including topotypical populations of five commonly used taxa, were studied genetically using partial sequences of the mitochondrial cytochrome c oxidase subunit I gene. Based on molecular data and the species concept we define, the following species and subspecies were identified: Hydrobia acuta acuta (Draparnaud, 1805) [=H. minoricensis (Paladilhe, 1875)], H. acuta neglecta Muus, 1963, and H. glyca (Servain, 1880) (=H. joossei van Aartsen, Menkhorst and Gittenberger, 1984). One population from Djerba, Tunisia (Hydrobia sp. A) and one population from Mallorca, Spain (Hydrobia sp. B) are genetically distinct from all other taxa studied here. Both populations potentially represent new species. Due to the fact that only one population each has been studied, and so the degree of variation within these two taxa cannot be assessed, a final decision regarding their species level cannot yet be made.
Keywords: Entomologie -- Djerba

« On va t’apprendre à faire des affaires… »: Échanges et négoces entre une anthropologue-photographe et des juives tunisiennes de Belleville - Conord, Sylvaine (Journal des anthropologues, 2000)
Keywords: Judaïsme -- Djerba

Restes de pressoirs à huile et à vin à Gighti et à Zarzis - Drine, Ali (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2000)
Keywords: Antiquité; Archéologie -- Zarzis